Karakteristik Peserta Didik dalam Proses Pembelajaran di SMK Nasional Berbah - Setiawan, Farid; Sabhara, Harun; Harmita, Harmita; Ariyanti, Leni (Lembaga Yasin AlSys, 2022)
Education is a learning process to develop the potential of a person or group in an effort to improve one's self-quality in changing attitudes and behavior through training and teaching. Of course, in improving the quality of a person, a management is needed in the education. So that education that is conceptualized properly and correctly will produce outputs that can keep pace with the current developments. Management is also required. Management is also needed as an effective thing in achieving a goal that has been in accordance with what has been planned because it is very effective in achieving goals and carrying out all work correctly and in an organized manner. With learning management in schools, creating concepts that have previously been designed for later learning, will result in success in educational goals, of course by utilizing quality human resources.